2021
DOI: 10.1016/j.neo.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Trop-2 induces ADAM10-mediated cleavage of E-cadherin and drives EMT-less metastasis in colon cancer

Abstract: We recently reported that activation of Trop-2 through its cleavage at R87-T88 by ADAM10 underlies Trop-2–driven progression of colon cancer. However, the mechanism of action and pathological impact of Trop-2 in metastatic diffusion remain unexplored. Through searches for molecular determinants of cancer metastasis, we identified TROP2 as unique in its up-regulation across independent colon cancer metastasis models. Overexpression of wild-type Trop-2 in KM12SM human colon cancer cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(99 citation statements)
references
References 46 publications
5
56
1
21
Order By: Relevance
“…4C, Supplementary Table 7). The difference in our observations compared to Guerra et al [ 20 ] who found an increase of TROP2 in metastatic lesions could be explained by the usage of different antibodies, the inclusion of a high number of rectal cancer, and the scoring approach. Otherwise, when analyzing the in silico dataset GSE41258 comparing the gene expression of TROP2 and ATF2 in non-paired 182 primary tumors and 47 liver metastasis, both markers showed a probe-dependent high variance in gene expression scores in both cohorts (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…4C, Supplementary Table 7). The difference in our observations compared to Guerra et al [ 20 ] who found an increase of TROP2 in metastatic lesions could be explained by the usage of different antibodies, the inclusion of a high number of rectal cancer, and the scoring approach. Otherwise, when analyzing the in silico dataset GSE41258 comparing the gene expression of TROP2 and ATF2 in non-paired 182 primary tumors and 47 liver metastasis, both markers showed a probe-dependent high variance in gene expression scores in both cohorts (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 99%
“…7F). Finally, these findings support previous reports from literature showing a pro-migratory role for TROP2 [ 20 , 23 , 24 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In cancer cells, Trop-2 overexpression stimulates growth and metastatic potential by promoting cell proliferation and migration. This protein is also involved in the epithelial-to-mesenchymal transition (EMT) since it determines E-cadherin down-regulation and vimentin expression, resulting in cell migration and stem cell-like properties [ 5 , 6 , 7 , 8 ]. Additionally, Trop-2 enhances cellular motility and invasion through the up-regulation of integrin-dependent signaling [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%